Why a management concept fails to support managers' work: The case of the 'core competence of a corporation'. Issue 1 (February 2017) - Schaupp, Marika; Virkkunen, Jaakko
Management concepts are both products and instruments of abstractive thinking. This conceptual article discusses the relationship between different forms of abstraction and the practical relevance of management concepts. It focuses on the difference between empirical and theoretical abstraction. The former serves to categorize while the latter serves to explain and construct. We argue that this distinction can partly explain the difficulties managers face when using the management concepts that researchers have introduced. To substantiate our claim, we analyse the creation and use of the concept of a corporation's core competence. The analysis shows how, in this case, a theoretical abstraction of a novel strategic principle turned into an empirical abstraction, which in practice has triggered unproductive attempts to categorize existing competencies rather than create new ones.